2007
DOI: 10.1002/bem.20307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12 mT static magnetic field on sympathetic agonist‐induced hypertension in wistar rats

Abstract: We investigated the combined effects of a moderate-intensity static magnetic field (SMF) and two different sympathetic agonists, an alpha(1)-adrenoceptor agonist, phenylephrine and a beta(1)-adrenoceptor agonist, dobutamine, which induced hypertension and different hemodynamics in Wistar rats. Five-week-old male rats were continuously exposed to the SMF intensity of 12 mT (B(max)) with the peak spatial gradient of 3 mT/mm for 10 weeks. A loop-shaped flexible rubber magnet was adjusted to fit snugly around the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…For a summary, please refer to Table 1. Okano and Ohkubo (2007) In particular, our series of studies [60][61][62][63][64][65][66][67], as shown in Table 1, have demonstrated that BP were modulated by moderate intensity SMF in mT level fields in pharmacologically treated animals and genetically hypertensive animals, while there was no change in normal, conscious animals when the values of the BP were within normal range (reference values). Therefore, we concluded that significant bioresponses to therapeutic signals occur when the deviations of the endpoints are far from homeostasis [77].…”
Section: Moderate Intensity Fieldsmentioning
confidence: 90%
See 4 more Smart Citations
“…For a summary, please refer to Table 1. Okano and Ohkubo (2007) In particular, our series of studies [60][61][62][63][64][65][66][67], as shown in Table 1, have demonstrated that BP were modulated by moderate intensity SMF in mT level fields in pharmacologically treated animals and genetically hypertensive animals, while there was no change in normal, conscious animals when the values of the BP were within normal range (reference values). Therefore, we concluded that significant bioresponses to therapeutic signals occur when the deviations of the endpoints are far from homeostasis [77].…”
Section: Moderate Intensity Fieldsmentioning
confidence: 90%
“…In a series of our later experiments [60][61][62][63][64][65][66][67], the previous works on the SMF effects on cutaneous microvasculature and microcirculation in conscious animals were extended. These studies focused on BP changes associated with SMF exposure.…”
Section: Moderate Intensity Fieldsmentioning
confidence: 99%
See 3 more Smart Citations